PEMELIHARAAN HUBUNGAN ANTARA ANAK REMAJA DENGAN ORANG TUA YANG BERCERAI - Azif, Zahra; Rahardjo, Turnomo; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
A complete and harmonious family is everyone's dream, but in fact it is not uncommon for incompatibility and problems to lead to divorce. Divorced couples who have children are vulnerable to destabilizing the relationship between parents and children. Parents have an important role to maintain and maintain their relationship with their children so that it continues to run well. Therefore, the role of relationship maintenance is needed to establish the sustainability of a relationship. This study aims to describe how the maintenance of relationships between adolescent children and divorced parents using two main theories, namely Relationship Maintenance Theory and Self-Disclosure Theory. The method used in this research is a qualitative research method with a phenomenological approach to uncover and dig deeper into the unique experiences that children have with divorced parents. This research utilizes in-depth interview techniques as a means of data collection.